A cargo of lead ingots from a shipwreck off Ashkelon, Israel 11th–13th centuries AD. (1st September 2019) - Galili, Ehud; Rosen, Baruch; Arenson, Sarah; Nir‐el, Yoram; Jacoby, David
Abstract: Shipwreck cargo of lead ingots, some marked, discovered off Tel Ashkelon, weighed about four tonnes. C14 analysis of charred wood from an ingot dated it to the 11th–13th centuries AD, Crusader times. Lead isotopic ratios provenanced the ingots to Mont‐Lozère, France. Various aspects of the lead trade are discussed, including: lead sources, extraction, casting, lead in the international maritime trade, weight units in medieval trade, prices, transportation, sale and storage, lead cargo and ballast, reconstruction of the wrecking event, salvage after the vessel was wrecked, Ashkelon as a trading coastal town in the 11th–13th centuries AD, and the possible destination of the cargo.